2017
DOI: 10.1177/1478077117738919
|View full text |Cite
|
Sign up to set email alerts
|

Usability of contemporary tools for the computational design of architectural objects: Review, features evaluation and reflection

Abstract: This article is an overview focused on functionality and usability of selected contemporary approaches for the computational floor plan generation of architectural objects. This article describes current solutions for generative architectural design and focuses on their usability from the point of view of architectural design practice. Recent research papers and prototypes, as well as the most important tools (selected computer-aided design and BIM software) for generative design from the architectural perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…The AFPG problem described in this article enables the exploration of architectural design space through the generation of architectural floor plans that meet certain specific design criteria. Similar approaches/ problems-a recent survey in Nisztuk and Myszkowski 12 -can be found in the literature.…”
Section: Related Workmentioning
confidence: 69%
See 2 more Smart Citations
“…The AFPG problem described in this article enables the exploration of architectural design space through the generation of architectural floor plans that meet certain specific design criteria. Similar approaches/ problems-a recent survey in Nisztuk and Myszkowski 12 -can be found in the literature.…”
Section: Related Workmentioning
confidence: 69%
“…A closer analysis and reviews can be found at Nisztuk and Myszkowski. 12 These applications can generally be divided into several groups enclosed in two main categories: with predetermined floor boundary outline, without the specified layout boundary envelope.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest grew in the use of SGs to formalize the important aesthetic issue of brand identity so that generated product designs would conform to it. In 2002, a 12-rule shape grammar was devised to capture the essence of Dove soap [19,43]. Two iconic vehicles, the Harley-Davidson motorcycle [7] and Buick car [44] were modeled using grammars of 45 and 63 rules, respectively.…”
Section: The Development Of Generative Product Design Systemsmentioning
confidence: 99%
“…Since a product can be anything manufactured by an enterprise for sale to customers [17], it is clear that this is a significant application area, as borne out by the fact that in the US alone, the 2019 consumer goods market had an estimated worth of $655 billion [18]. Review papers exist for architectural GD systems (e.g., [19,20]) but there are none specifically for product design. The current paper aims to address this.…”
Section: Introductionmentioning
confidence: 99%